If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(-2x-5)=-5
We move all terms to the left:
-(-2x-5)-(-5)=0
We add all the numbers together, and all the variables
-(-2x-5)+5=0
We get rid of parentheses
2x+5+5=0
We add all the numbers together, and all the variables
2x+10=0
We move all terms containing x to the left, all other terms to the right
2x=-10
x=-10/2
x=-5
| 6x-6+4x+6=180 | | 48-3x=90 | | 4(x-2)-16=3(x-1) | | (450/3x)=6+x | | 5a-2(-7a-10)=128 | | 112=4(6)(4)+2(4)h | | 7n=-61.6 | | 0.7·(t+4)=4.9 | | 450/3x=6+x | | -43=-5c+4(2c+7 | | 2w+10=2w+1 | | 12^y-2=20 | | 220=4(9)h+2(5)h | | 2x-111+x+9=x | | 4^2z=40 | | 87=y/3 | | 5t-2(5t+10)=100 | | 4(2y-10)=8 | | 2x-54=114 | | 9^y-2=20 | | 2(w+4)=20 | | 0.40x+0.05(10-x)=0.10(-9) | | 4x/3+3=x | | 2p+13=3. | | 3(4x-3)=10 | | 2x-(5x-3)=10 | | 5x2+6x+2=12 | | T+5t=24 | | X2+9x-6=0 | | 9x2+4x-6=0 | | 2x2+9x-7=0 | | 5=5/9(y-32) |